2019
DOI: 10.2147/ppa.s205686
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Parental acceptance of the utilization of silver diamine fluoride on their child’s primary and permanent teeth</p>

Abstract: Purpose: Silver diamine fluoride (SDF) is an effective caries control agent. The aim of our study was to investigate the parental acceptance of the utilization of SDF on their child’s primary and permanent teeth and to determine the factors that influence their decision-making. Patients and methods: This descriptive cross-sectional study included parents of healthy children aged 12 years and younger and currently receiving dental treatment. The interview questionnaire was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
70
4
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 10 publications
8
70
4
9
Order By: Relevance
“…20 Although discoloration caused by SDF was unacceptable to most of the parents, many would still choose SDF instead of pharmacological methods like sedation or general anesthesia. These results were similar to the study done by Bagher, 15 wherein parents of children with history of uncooperative behavior during previous dental treatment were significantly accepting SDF regardless of type and location of teeth. The reason for choosing SDF may be the parent's awareness of anesthetic agents being associated with potential risk to patient's overall health with some reports of morbidity and mortality.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…20 Although discoloration caused by SDF was unacceptable to most of the parents, many would still choose SDF instead of pharmacological methods like sedation or general anesthesia. These results were similar to the study done by Bagher, 15 wherein parents of children with history of uncooperative behavior during previous dental treatment were significantly accepting SDF regardless of type and location of teeth. The reason for choosing SDF may be the parent's awareness of anesthetic agents being associated with potential risk to patient's overall health with some reports of morbidity and mortality.…”
Section: Discussionsupporting
confidence: 90%
“…These results were in conjunction to the study done by Crystal 14 and Bagher. 15 However, contrasting results were reported by Alshammari 16 where majority of the parents strongly refused SDF treatment both in front and back teeth. Also, other authors have reported that parents preferred tooth-colored restorations over amalgams and silver metal crowns 17 and zirconia esthetic crowns over other anterior restorations.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This study gains broader importance toward the realization of population health goals when considered within the contexts of its use, including evidence on the acceptability of SDF among diverse patient groups [23][24][25][26][27][28][29]. Findings indicate how this noninvasive, cost-effective, setting-exible treatment may be understood as a meaningful option that providers can con dently consider based on patient characteristics, treatment goals, and other factors.…”
Section: Discussionmentioning
confidence: 96%
“…The existing literature on SDF focuses primarily on young children who still have primary dentition [10,13,15,[22][23][24][25][26][27][28] and older adults [16,30], often omitting older children, adolescents, and working-age adults. The strongest evidence on SDF derives from randomized controlled trials (RCTs) whether individual or aggregated into evidence reviews, which compare SDF with placebo or other treatments, limit the intervention to SDF alone versus when used in combination with restorative procedures, and generate ndings from samples treated under ideal clinical conditions and from analyses that control for covariates [6,[10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%